2020
DOI: 10.7554/elife.53080
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-wide analysis of a malaria vaccine study reveals personalized humoral immune profiles in Tanzanian adults

Abstract: Tanzanian adult male volunteers were immunized by direct venous inoculation with radiation-attenuated, aseptic, purified, cryopreserved Plasmodium falciparum (Pf) sporozoites (PfSPZ Vaccine) and protective efficacy assessed by homologous controlled human malaria infection (CHMI). Serum immunoglobulin G (IgG) responses were analyzed longitudinally using a Pf protein microarray covering 91% of the proteome, providing first insights into naturally acquired and PfSPZ Vaccine-induced whole parasite antibody profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…In addition, the high expression of IGHG2 and IGHG4 might demonstrate that IgG2 and IgG4 are the main type of IgG induced by CoronaVac. Previous multifactorial models have also revealed integrated networks on humoral immunity induced by vaccination against various other diseases (Camponovo et al, 2020; Li et al, 2014; Li et al, 2017; O’Connor et al, 2017). For instance, herpes zoster (HZ) induced changes in genes and metabolites associated with adaptive immunity and showed that sterol metabolism was tightly coupled with immunity (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the high expression of IGHG2 and IGHG4 might demonstrate that IgG2 and IgG4 are the main type of IgG induced by CoronaVac. Previous multifactorial models have also revealed integrated networks on humoral immunity induced by vaccination against various other diseases (Camponovo et al, 2020; Li et al, 2014; Li et al, 2017; O’Connor et al, 2017). For instance, herpes zoster (HZ) induced changes in genes and metabolites associated with adaptive immunity and showed that sterol metabolism was tightly coupled with immunity (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Blood proteomics and metabolomics have provided valuable insights into the early events of vaccine-induced immune response (Best et al, 2018; Camponovo et al, 2020; Rieckmann et al, 2017). For example, proteomic signatures after vaccination have been used to predict vaccine-induced T cell responses in multiple studies, and different classes of vaccines have been shown to induce distinct protein expression patterns (Camponovo et al, 2020). The coordinated action of the immune system induced by vaccines resembles a social network.…”
Section: Introductionmentioning
confidence: 99%
“…Preexisting immune responses, acquired actively through prior exposure to malaria parasites in vivo or in utero, or -in the case of infants-passively acquired antibodies, may mask vaccine-induced immune responses and vaccine efficacy. Preexisting immunity can also impact on vaccine-induced responses through 'natural imprinting', as was recently observed in a PfSPZ Vaccine study in Tanzanian adults [208]. These subjects' seroreactivity profile remained largely unchanged following repeated vaccination, suggesting that only preexisting antibody responses were boosted.…”
Section: Challenges Related To Vaccine Correlates In Field Studiesmentioning
confidence: 63%
“…To deconvolve this will likely require further examination at single B cell level, where direct affinity/functional relationships can be determined, as we have done for RAM1 and RAM2. Indeed, in studies of natural infection and whole sporozoite vaccination, only a tiny fraction of antibodies obtained are functional against the parasite, implying that potent functional antibodies are rare in the overall B cell repertoire (Camponovo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Subunit vaccines, such as RTS,S and R21, induce potent antibody responses against the major surface protein on the sporozoite, the C ircum s porozoite P rotein (CSP) (Datoo et al, 2021; Sun et al, 2003). Whole sporozoite vaccines also elicit anti-CSP antibodies, they also produce antibodies to other Plasmodium antigens (Camponovo et al, 2020; Mordmuller et al, 2017).…”
Section: Introductionmentioning
confidence: 99%